NEW APPROACHES TO REFORM IN THE HIGHER EDUCATION SYSTEM (Scientific journal of the Fergana State University, 2025)
The higher education system has been a major factor in the scientific, cultural and economic development of every society. Every country strives to increase its economic potential by coordinating, developing and upgrading its education system.Reforms and new approaches in the higher education system have become one of the most important issues today. Many countries and regions are trying to modernize their higher education systems, as this education system plays an important role in the economic and social development of a country, as well as in ensuring competitiveness in the field of science and technology.Reforms in the higher education system serve to ensure not only the quality of education, but also the worldview of young people and their active participation in the life of society. Through new approaches, Uzbekistan seeks not only to improve its domestic education system, but also to take a strong place in the international arena.Reforms and new approaches in the higher education system are helping to modernize the education sector in Uzbekistan. This process not only improves the quality of education, but also strengthens the country’s position in the global education systemIn the article we talk about the main directions of reforms and new approaches in the higher education system and what practical evidence they are based on